PERANAN LITERASI MEDIA DIGITAL DALAM MENCEGAH PENYEBARAN HOAKS - Ramayanti, Rory; Sa'diyah, Lailatus (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2017)
This paper aims to describe and ppreciate various efforts that have been done by the Indoneian government to design the prevention and eradication of to distribution of false information (hoaks), such as (i) Rules of informtion laws and electronic transaction (UU ITE) which gives smoe santions for internet users who distribute negative content and hoaks ; and (ii) release a communication and information ministry regulation number 19 of 2014 about blocking and screening sites and developing a system “TRUST” + Positive” system which the system provides a list of negatively charged sites, but this article also provides a critical note to note from both of it. This paper also emphasize that there are still many thinsg tht can be considered to improve the effectiveness of prevention digital literacy for the community. Reading very rapid and limitless information and tools communication used to obtain such information through digital literacy.